Probe-based confocal laser endomicroscopy versus biopsies in the diagnostics of oesophageal and gastric lesions: A prospective, pathologist-blinded study - Kollar, Marek; Krajciova, Jana; Prefertusova, Lucia; Sticova, Eva; Maluskova, Jana; Vackova, Zuzana; Martinek, Jan (United European gastroenterology journal, 2020)
BACKGROUND AND AIM: Probe-based confocal laser endomicroscopy (pCLE) provides real-time microscopic visualisation. Our aim was to compare the diagnostic accuracy of pCLE with standard biopsies in patients with visible oesophageal or gastric lesions. METHODS: This was a single-centre, prospective, pathologist-blinded study. Patients underwent high-resolution endoscopy, and lesions were examined by pCLE followed by standard biopsies. A definitive diagnosis was determined from resection specimen. Main outcomes were overall diagnostic accuracy, sensitivity, specificity and positive and negative predictive values. RESULTS: We examined 74 lesions in 67 patients. Definitive diagnoses revealed 34 malignant and 40 non-malignant lesions. pCLE diagnosis was correct in 89.2% (66/74), while diagnosis based on biopsy was correct in 85% (57/67; p = 0.6). The overall diagnostic accuracy of biopsies was 85% (76-94%) and that of pCLE was 89% (79-96%). pCLE correctly diagnosed malignant lesions, comprising oesophageal adenocarcinoma, oesophageal squamous-cell cancer or gastric adenocarcinoma, in 88.2% (30/34) of cases, while biopsy was correctly diagnosed in 75.9% (22/29; p = 0.3). Sensitivity and specificity to diagnose a malignant lesion were 75.9% (95% confidence interval (CI) 56-89%) and 100% (95% CI 90-100%) for biopsies and 88.2% (95% CI 72-97%) and 92% (95% CI 79-98%) for pCLE. No differences between biopsies and pCLE were found with regard to sensitivity, specificity to diagnose dysplastic and benign lesions (p > 0.2). CONCLUSION: pCLE provides satisfactory diagnostic accuracy comparable with standard biopsies in patients with oesophageal or gastric lesions. ClinicalTrials.gov identifier: NCT0292049).
Keywords: dospělí; Carcinoma, Squamous Cell; Female; žaludeční sliznice; Adult; ženské pohlaví; biopsie; Gastric Mucosa; lidé; Esophageal Neoplasms; Sensitivity and Specificity; Stomach Neoplasms; Aged, 80 and over; gastrointestinální endoskopie; senzitivita a specificita; nádory jícnu; sliznice jícnu; Lasers; prospektivní studie; Adenocarcinoma; Endoscopy, Gastrointestinal; Esophageal Mucosa; Male; Aged; Prospective Studies; spinocelulární karcinom; nádory žaludku; adenokarcinom; Biopsy; lasery; lidé středního věku; senioři nad 80 let; senioři; mužské pohlaví; Microscopy, Confocal; konfokální mikroskopie; Middle Aged; Humans